L’autonarration en tant que méthode d’investigation sur la compétence plurilingue - Kucharczyk, Radosław; Szymankiewicz, Krystyna (Studia Romanica Posnaniensia, 2019)
This article proposes a reflection on the usefulness of the autonarration method for research in language didactics and plurilingualism. Starting from a definition of the autonarration relating to the field of teaching / learning of languages and cultures, we then explain the specificity of the plurilingual competence to justify the choice of the autonarration as a method well adapted to the study of learning to aim at the development of such a competence. We then present the types of autonarration practised and their functions as well as possible difficulties for research. Our words are supported by examples of research whose purpose was to examine the impact of plurilingual competence in the teaching / learning languages.